2012
DOI: 10.1007/s00359-012-0711-8
|View full text |Cite
|
Sign up to set email alerts
|

Vibration detection and discrimination in the masked birch caterpillar (Drepana arcuata)

Abstract: Leaf-borne vibrations are potentially important to caterpillars for communication and risk assessment. Yet, little is known about the vibratory environment of caterpillars, or how they detect and discriminate between vibrations from relevant and non-relevant sources. We measured the vibratory ‘landscape’ of the territorial masked birch caterpillar Drepana arcuata (Drepanidae), and assessed its ability to detect and respond to vibrations generated by conspecific and predatory intruders, wind and rain. Residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…Such freezing is presumed to be advantageous for detecting vibrations as well as visual and olfactory information necessary for recognizing conspecifics or predators. The freeze response has also been demonstrated in a territorial leafdwelling caterpillar, D. arcuata (Yack et al, 2001;Guedes et al, 2012); the caterpillars stop feeding and constructing shelters (i.e., freeze) in response to vibrations from approaching intruders and begin signaling as intruders approach (Guedes et al, 2012). Similar to caterpillars, beetles can receive vibrational information from approaching con-or heterospecifics and determine the next behavioral step, such as walking or flight for escape, preceding freeze and/or startle responses.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Such freezing is presumed to be advantageous for detecting vibrations as well as visual and olfactory information necessary for recognizing conspecifics or predators. The freeze response has also been demonstrated in a territorial leafdwelling caterpillar, D. arcuata (Yack et al, 2001;Guedes et al, 2012); the caterpillars stop feeding and constructing shelters (i.e., freeze) in response to vibrations from approaching intruders and begin signaling as intruders approach (Guedes et al, 2012). Similar to caterpillars, beetles can receive vibrational information from approaching con-or heterospecifics and determine the next behavioral step, such as walking or flight for escape, preceding freeze and/or startle responses.…”
Section: Discussionmentioning
confidence: 93%
“…An increasing number of studies have shown that arthropods inhabiting plants detect approaching predators, prey, or conspecifics through substrate-borne vibrations (Ota and Č okl, 1991;Bacher et al, 1997;Djemai et al, 2001;Yack et al, 2001;Djemai et al, 2004;Castellanos and Barbosa, 2006;McNett et al, 2010;Eriksson et al, 2011;Guedes et al, 2012). Michelsen et al (1982) noted that plant stems and leaves serve as channels for transmitting and receiving vibrational information.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In crickets or tettigoniid, species-specific vibratory signals can facilitate orientation in a complex 3D habitat, like bushes, toward conspecifics (Latimer and Schatral 1983;Stiedl and Kalmring 1989;Weidemann and Keuper 1987). Holometabolous caterpillars can detect and discriminate vibratory signals occurring on leaves with so far unidentified sense organs (Guedes et al 2012).These exemplary observations show the ability of various species to locate vibrational stimuli.…”
Section: Neural Network and Neuroethologymentioning
confidence: 95%
“…It is known that natural sources of vibratory noise, such as those caused by rain, wind and animal songs, play important roles in modulating the aforementioned behaviours. Some organisms can discriminate between noise and 'biological' cues even when both contain overlapping spectra (Caldwell, McDaniel, & Warkentin, 2009Guedes, Matheson, Frei, Smith, & Yack, 2012). However, many other organisms are subject to vibratory noise interference.…”
mentioning
confidence: 99%